Is travel behaviour an equity issue? Using GPS location data to assess the effects of income and supermarket availability on travel reduction during the COVID-19 pandemic. Issue 3 (3rd July 2021) - Liu, Jody; Gross, James; Ha, Jaehyun
ABSTRACT: With recent research identifying mobility restrictions for alleviating the spread of COVID-19, governments have implemented stay-at-home measures, which in turn produced significant changes in people's travel behaviours. Despite these orders, however, people still have to make trips for work or to acquire essential goods. To better understand how these necessary trips influenced changes in individual mobility due to the pandemic, this study focused on the relationship between trip frequency and distance to median incomes, as well as between trip frequency and distance to supermarket density. We made use of the University of Maryland COVID-19 Impact Analysis Platform as our primary source for GPS travel data to study mobility changes at the county-level across the U.S.A. Results showed that trip frequency and distance were significantly different before the outbreak of COVID-19 and during three peak periods of COVID-19 infection. Specifically, we found the reduction of both frequency and distance of trips is negatively correlated to both median income and supermarket density. Thus we conclude that individual choice in adherence to staying-at-home is less dependent on the lockdown measures and more influenced by financial capacity and access to necessary goods and services. These findings could help inform policy development and programmatic responses to help people reduce their mobility. For example, government authorities might consider monthly stimulus or other financial support programs that would allow people greater access to delivery services. In the future, urban planners and policymakers should address the root causes that lead to such economic disparities and food insecurities, in order to build resilience in the face of possible future pandemics.